Modelling and Optimizing of Joint’s Fracture Toughness between A7075-T651 and AZ31B Dissimilar Alloys Welded by GMA Spot Welding Method - M. I., Rafiquel; M., Ishak (scientific.net, 2014)
Innovative technologies in dissimilar welding for lightweight metals like aluminium and magnesium alloys would achieve weight reduction, high specific strength, fuel efficiency and less environmental pollution in automobiles, aviation and marine industries. The objective of this research was to investigate, model and optimize the fracture toughness (FT) of lap weld joint between A7075-T651 aluminium and AZ31B magnesium alloys welded by gas metal arc (GMA) spot welding method using ER308L stainless steel filler. The FT of the welding joint was calculated from yield strength and absorbed charpy impact energy of the joints using Rolfe-Novak-Barsom correlation and was compared with the FT of AZ31B parent metal. The results showed that, maximum FT up to 93.08% of the FT of AZ31B parent metal can be achieved. The mathematical model had high accuracy to predict the FT and the optimization for FT has been matched with the validation test.